Critical success factors of operational excellence practices for manufacturing industry. (22nd January 2021) - Wahab, Mohd Hafeez Al-Amin Abdul; Ismail, Mohammad; Muhayiddin, Mohd Nazri
This study examines the critical success factors (CSFs) of operational excellence practices in the manufacturing industry. The survey questionnaires were designed and distributed to the 50 respondents. The pilot study sample consists of 30 respondents from 50 questionnaires, with an average response rate of 60%. The reliability and validity test was conducted and the data were analysed using the statistical software SPSS version 22. The results indicate that six factors have been identified to be critical factors for operational excellence practices. Furthermore, the process management is the most critical factor influencing the operational excellence practices implementation success. This research concluded that the manufacturing industry should implement six critical success factors of operational excellence practices to enhance the organisational performance. Thus, further studies are recommended to investigate and validate the structural relationship between operational excellence practices and sustainable performance in Malaysian manufacturing industry.